The Impact of Effective Performance Management system on Employee Outcomes; Evidence from the Hoteling industry of Pakistan - Khan, Chakar; Rizvi, Syed Tahir Hussain; Ahmed , Mansoor; Imran Farooq, (IBT- JOURNAL OF BUSINESS STUDIES, 2024)
The study's objective is to examine the impact of performance on the employee’s behavior. The proposed agent-based model (ABM) is inspired by Guest (1997) within formal organizational structure frameworks that connect HRM and organizational performance to employee outcomes through performance management. Performance management was taken as the explanatory variable, and Employee outcomes were used as the explained variable. The sampling technique used was cluster sampling. The data was collected through designed questionnaires from 250 hotel employees across the provincial capital cities of Pakistan, including Islamabad, in 2023. Correlation and descriptive statistics were used in quantitative analysis. The regression was employed to estimate the data. In addition, ANOVA, R Square, standard error of the estimate, and Cronbach's are applied to check the model's significance, power, accuracy of prediction, and validity. A strong and positive relationship exists between Performance management and Employee outcomes. Organizations can positively impact employee outcomes by implementing effective performance, leading to a more productive, engaged, and successful workforce.